Malaysia-ASEAN trade determinants, patterns and prospects - Armi, Mohmed Jalwar (2015)
The main objective of this study is to analyze the factors that effect Malaysia – ASEAN trade during 1980 – 2014. The (9) ASEAN countries such as Brunei, Indonesia, Thailand, Singapore, Vietnam, Cambodia, Myanmar, Philippines and Lao PDR. There are five different panel unit root test have been applied to check the stationarity issues the five test are {LLC test – Beritung test - IPS test – F ADS test – F-PP test}. The results of panel unit root tests shows that all the variables are stationary at level and become non-stationary at first difference. In addition, results of Granger causality suggested that in the short run unidirectional Granger causalities were found to be running from per capita GDP and exchange rate of Malaysia total trade between Malaysian and other ASEAN countries, as well as from total population of other ASEAN countries to total trade. For joint tests, bi-directional causalities were observed between per capita GDP of Malaysia, per capita GDP of other ASEAN countries, exchange rate of Malaysia, exchange rate of other ASEAN countries, total population of other ASEAN countries, distance between capital of Malaysia and capital of other ASEAN countries and total trade between Malaysia and other ASEAN countries. In other words all the variables are reliant to each other. The results of GMM model show that per capita GDP of Malaysia and other ASEAN countries as well as exchange rate of Malaysia and other ASEAN countries are positively and statistically significant. However, total population of other ASEAN countries is insignificant even at 10 percent level of significant. Similarly, total distance between capital of Malaysia and other ASEAN countries is negatively significant. An increase of Gross Domestic Product (GDP) of Malaysia and other ASEAN countries as well as exchange rate of Malaysia and other ASEAN countries will increase it will also boost the trade between Malaysia and other ASEAN countries. Consequently, increase the distance between capital of Malaysia and other ASEAN countries will decrease the trade between Malaysia and other ASEAN countries